Zachary Scott : Hollywood's Sophisticated Cad - Davis, Ronald L. (Book collections on Project MUSE., 2009)
Throughout the 1940s, Zachary Scott (1914-1965) was the model for sophisticated, debonair villains in American film. His best-known roles include a mysterious criminal in The Mask of Dimitrios and the indolent husband in Mildred Pierce. He garnered further acclaim for his portrayal of villains in Her Kind of Man, Danger Signal, and South of St. Louis. Although he earned critical praise for his performance as a heroic tenant farmer in Jean Renoir's The Southerner, Scott never quite escaped typecasting. In Zachary Scott: Hollywood's Sophisticated Cad, Ronald L. Davis writes an appea.